RNA-guided integration of diverse DNA molecules by casposase-Cas9 fusions - Lau, Chun H. (2020)
Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR associated (Cas) proteins build adaptive immunity against mobile genetic elements (MGEs) in prokaryotes. The memory of previously encountered MGEs is established by DNA capture and integration into CRISPR loci catalysed by Cas1-Cas2 adaptation complexes. Cas1 is thought to have evolved from enzymes called casposases, which belong to a novel class of transposases. A previous study showed casposases integrate into target molecules single and double stranded DNA containing terminal inverted repeats (TIRs). In this project, in vitro biochemical assays showed that the substrate flexibility of Acidoprofundum boonei casposase extends to random integration of DNA without TIRs, including integration of a functional gene. The DNA substrate tolerance of casposases may make them useful as a tool for biotechnology applications that require targeted DNA integration activity. Casposase-Cas9 fusions were engineered to investigate the targeting of DNA integration to specific DNA sites. The fusion proteins were able to form an R-loop with target DNA and demonstrated RNA-guided DNA integration in vitro. Full-site RNA-guided DNA integration products were not detected and DNA integration into some non-specific DNA sites was observed. Expression of fusion proteins in Escherichia coli cells could target both chromosomal and plasmid lacZ gene but casposase catalysed DNA integration was not detected. Casposase-Cas9 fusions might be a useful prototype of a genome editing tool for targeted DNA insertion that is independent of homology-directed DNA repair. In addition, the project investigated alternatives to casposase-Cas9 fusions. A casposase-dCasX fusion construct yielded protein that could not be successfully purified. A tyrosine recombinase, IntpTN3 integrase, was fused to dCas9 and successfully purified. However, RNA-guided recombination between homologous sequences was not detected. Future work will require a deeper understanding of the low sequence specificity recombination activity of IntpTN3.